UNIVERSITY STUDENTS’ ATTITUDES TOWARD SEEKING PSYCHOLOGICAL HELP ACCORDING TO THEIR PERSONALITY TRAITS - Hatice KUMCAĞIZ (Fırat University, 2019)
This study examined the relationship between university students’ attitudes toward seeking psychological help with respect to their personality traits. The study was conducted with 1132 students of 1st, 2nd, 3rd and 4th grades studying at various departments at Ondokuz Mayıs University. The study used the Eysenck Personality Questionnaire-Revised Short Version, adapted into Turkish by Karancı, Dirik and Yorulmaz (2007) to identify the personal traits of students, and the Attitudes Toward Seeking Psychological Help Scale-Short Version developed (1997) and revised (2004) by Türküm to examine student’s attitudes toward seeking psychological help. The Spearman correlation coefficient was used due to the non-parametric distribution of data. The findings indicated that as students’ scores of the extraversion dimension of personality increased, so did their level of attitudes toward seeking psychological help. On the contrary, while students’ scores of the psychoticism dimension of personality decreased, their level of attitudes toward seeking psychological help increased. No statistically significant relationship was found between the neuroticism dimension of personality and their attitudes toward seeking psychological help. Finally, as students’ scores of the lie dimension of personality increased, so did their level of attitudes toward seeking psychological help.